1997
DOI: 10.1094/pdis.1997.81.8.867
|View full text |Cite
|
Sign up to set email alerts
|

SalmonellaContamination Associated with Bacterial Soft Rot of Fresh Fruits and Vegetables in the Marketplace

Abstract: Wash water from 66% of 401 samples of fresh fruits and vegetables collected in the marketplace and affected by bacterial soft rot were positive for suspected strains of Salmonella, i.e., black, hydrogen sulfide-positive colonies on Salmonella-Shigella agar incubated for 24 h at 37°C. By comparison, 30% of 402 healthy samples were positive. Incidence of suspected Salmonella in broth enrichment cultures was 59% in 533 soft rotted samples and 33% in 781 healthy samples. Thirty percent of 166 representative strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(118 citation statements)
references
References 17 publications
4
111
2
Order By: Relevance
“…in pawpaw, orange and kola nut at Sango Market, Ilorin. However, this finding contradicts the work of Wells and Butterfield [17] who reported Salmonella, Shigella and gastro-intestinal viruses as the major pathogens associated with food poisoning in England and the United States.…”
Section: Discussioncontrasting
confidence: 77%
“…in pawpaw, orange and kola nut at Sango Market, Ilorin. However, this finding contradicts the work of Wells and Butterfield [17] who reported Salmonella, Shigella and gastro-intestinal viruses as the major pathogens associated with food poisoning in England and the United States.…”
Section: Discussioncontrasting
confidence: 77%
“…It is well established that the incidence of S. Enteritidis on fresh produce is significantly higher on injured produce (Wells et al, 1997;Wells et al, 1999). This study did not show the internalization and existence of Salmonella in the fruits of tomato plants cultivated in soil contaminated with Salmonella.…”
Section: Discussioncontrasting
confidence: 75%
“…49 Furthermore, a survey of supermarket produce revealed that Salmonella incidence on produce was twice as likely in the presence of a soft rot plant pathogen, Erwinia carotovora, which is now known as Pectobacterium carotovora. 67 It is hypothesized that human pathogens, including Salmonella, may depend on the presence of plant associated bacterial and fungal organisms to provide carbon and energy sources through the degradation of plant cell wall polymers. 68 Unfortunately, current research methods cannot address all of the factors involved in enteric and plant interactions, but the studies highlight the influences of each factor to better understand the overall interactions in the plant system.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple factors involved in the interaction between Salmonella spp and produce including the produce type, cultivar and physiological state of the plant. 49,66,67 Differential contamination of produce commodities was observed when produce was exposed to Salmonella spp through contaminated soil. The seedlings of the Brassicaceae family, including radishes, turnips and broccoli, had a higher prevalence of Salmonella spp than the lettuce, carrot and tomato crops.…”
Section: Salmonella Spp Survival In the Plant Environmentmentioning
confidence: 99%